Chip formation in the machining of SiC-particle-reinforced aluminium-matrix composites - Lin, J.T.; Bhattacharyya, D.; Ferguson, W.G. (Composites science and technology, 1998)
As a consequence of the widening range of applications of metal-matrix composites (MMCs), the machining of these materials has become a very important subject for research. Aluminium-matrix composites are widely used for their favourable specific strength/stiffness and corrosion resistance properties. This paper describes a study of chip formation during the machining of a DURALCAN ® aluminium-matrix composite (A359/SiC/20p). For good machinability, it is desirable to have continuous chips in short segments without the use of a chip breaker. The chip-formation mechanism in machining this silicon-carbide-particle-reinforced aluminium MMC at three different cutting speeds has therefore been investigated by using an explosive charged quick-stop device. An improved quick-stop device has enabled research to be carried out more easily on the mechanism of chip formation by achieving better chip control during machining. During the chip-breaking process, the primary chip-forming mechanism involves the initiation of cracks from the outer free surface of the chip due to the high shear stress. Meanwhile, some small voids are formed by the separation of particles and the matrix material within the chip because of the stress concentration at the edges of the particles. The crack propagation is enhanced through the coalescence of these voids along the shear plane. The fracture and sliding of material then follow to form semicontinuous ‘saw-toothed’ chips.